Prinsip Pengelolaan Piutang: Strategi Efektif untuk Meningkatkan Arus Kas Perusahaan - Rojak, Fadel Mohamad; Fariz, Luthfi Ahmad; Husen, Dadang Sobana (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
Receivables management is a crucial aspect in a company's financial management that functions to ensure smooth and stable cash flow. This study aims to explore the principles and effective strategies in receivables management, with a case study on PT Indofood Sukses Makmur Tbk. Through a qualitative approach and literature review techniques, this study analyzes credit policies, collection procedures, and the use of technology in receivables management. The results of the study show that the implementation of strict policies and effective monitoring can minimize the risk of losses due to uncollectible receivables. In addition, continuous evaluation and improvement in receivables management is very important to maintain cash flow stability and support company growth. Thus, effective receivables management contributes to business sustainability and investor confidence